Experimental Analysis of Volume Flow Rate in Water Chiller Type of Central AC System - Wirajati, IGAB (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009)
Central AC chilled water system is an air conditioning system that has cooling ability in more than one room. The system has two cycles consist of primary and secondary cycles. When primary cycle works, the refrigerant is used as a working fluid while in the secondary cycle process, the water is used as working fluid. To determine the heat absorbed by water, it can be done by analyzing NTU (Number of Transfer Unit) of the water chiller system. The variation of the chilled water volume rate applied in this research was from 13 l/min to 5 l/min, with the interval of 0.5 l/min. As a result, it was founded that the maximum value of NTU was 2.01, at chilled water volume rate of 12 l/min. Below that chilled water volume rate, values of NTU would decrease and stable. It can be concluded that the volume rate of chilled water influenced the value of NTU in the FCU (Fan Coil Unit) of the water chiller AC system.
Keywords: AC central chilled water system, Flow rate of volume, Chilled water, NTU